Glycopeptide Mimetics Recapitulate High‐Mannose‐Type Oligosaccharide Binding and Function1. (16th March 2015) - Lusvarghi, Sabrina; Ghirlando, Rodolfo; Wong, Chi‐Huey; Bewley, Carole A.
Abstract High‐mannose‐type glycans (HMTGs) decorating viral spike proteins are targets for virus neutralization. For carbohydrate‐binding proteins, multivalency is important for high avidity binding and potent inhibition. To define the chemical determinants controlling multivalent interactions we designed glycopeptide HMTG mimetics with systematically varied mannose valency and spacing. Using the potent antiviral lectin griffithsin (GRFT) as a model, we identified by NMR spectroscopy, SPR, analytical ultracentrifugation, and microcalorimetry glycopeptides that fully recapitulate the specificity and kinetics of binding to Man9GlcNAc2Asn and a synthetic nonamannoside. We find that mannose spacing and valency dictate whether glycopeptides engage GRFT in a face‐to‐face or an intermolecular binding mode. Surprisingly, although face‐to‐face interactions are of higher affinity, intermolecular interactions are longer lived. These findings yield key insights into mechanisms involved in glycan‐mediated viral inhibition.